Linguistic variation in subtitling for audiovisual media in Portugal: case study of the film Gone with the Wind - Lopes Cavalheiro, Lili (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Film subtitling involves per se a number of constraints. However, when characters speak with a particular dialect or accent, the task is even more complex. Linguistic variation is a key factor in depicting a film character and the translator will consider the implications of his/her choice when translating into the Target Culture, since such sociolinguistic and/or idio-syncratic language features contribute to the meaning(s) of a film. The presence of linguistic variation may be tied in with the medium through which a film is distributed; hence translating for different media may imply the application of different strategies. This article will analyze the film subtitling of Gone with the Wind (1939), in particular how Mammy’s speech is translated into Portuguese for RTP (public television channel), TVI (private television channel), VHS and the Internet, while also searching for translational regularities.